2020
DOI: 10.1177/2309499020905711
|View full text |Cite
|
Sign up to set email alerts
|

A portable pneumatic compression device to prevent venous thromboembolism in orthopedic patients with the highest risks of both venous thrombosis and bleeding: A case series study

Abstract: Purpose: There is a pressing need for safe venous thromboembolism (VTE) prophylaxis in orthopedic patients with the highest risks of both venous thrombosis and bleeding. Portable intermittent pneumatic compression device (IPCD) has proven to be effective and safe in patients with a high risk of venous thrombosis and low bleeding risk. Therefore, this study examined the effectiveness, safety, and wearing compliance of portable IPCD for postoperative VTE prophylaxis in patients with the highest risks of both ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
0
14
0
1
Order By: Relevance
“…lower limb elevation and deep breath) and chemoprophylaxis (subcutaneous injection of low molecular weight heparin, 2500-4100 IU, once daily). All patients routinely received Intermittent Pneumatic Compression Devices(IPCD)to prevent thrombosis [ 14 , 15 ]. For patients allergic to LMWH, oral rivaroxaban was administered at a dosage of 10 mg once daily.…”
Section: Methodsmentioning
confidence: 99%
“…lower limb elevation and deep breath) and chemoprophylaxis (subcutaneous injection of low molecular weight heparin, 2500-4100 IU, once daily). All patients routinely received Intermittent Pneumatic Compression Devices(IPCD)to prevent thrombosis [ 14 , 15 ]. For patients allergic to LMWH, oral rivaroxaban was administered at a dosage of 10 mg once daily.…”
Section: Methodsmentioning
confidence: 99%
“…In a case series of 38 patients who underwent lower extremity orthopedic surgery with the highest risk of both venous thrombosis and bleeding, a portable pneumatic compression device was used to prevent VTE [ 44 ]. The results showed that the incidence of asymptomatic DVT was 5.3%, and that of symptomatic DVT was 2.6% [ 44 ]. No major bleeding or adverse events were observed [ 44 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…The results showed that the incidence of asymptomatic DVT was 5.3%, and that of symptomatic DVT was 2.6% [ 44 ]. No major bleeding or adverse events were observed [ 44 ]. Also, a retrospective study reviewed all patients with hemophilia A or B who underwent primary TKA and THA using a mechanical prophylaxis without chemoprophylaxis [ 45 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…The CCDSS is a decision-making system that works in 3 steps. [ 20 ] First, the VTE risk level in each type of surgery is categorized. Second, the system automatically adds the risk score for 16 additional VTE risk factors (eg, background factors and patient history) to determine the VTE risk level, and the risk factors are listed with weights of −2 to 8 points each.…”
Section: Methodsmentioning
confidence: 99%